1997
DOI: 10.1002/chin.199723258
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Trypanocidal Activity of Synthetic Heterocyclic Derivatives of Active Quinones from Tabebuia sp.

Abstract: Trypanocidal Activity of Synthetic Heterocyclic Derivatives of Active Quinones from Tabebuia sp.-The reaction of lapachol (I) and lapachones (VII), (XII) with glycine, ethyl α-aminoacetate and ammonium/benzaldehyde generates nitrogen heterocyclic compounds. The reaction and work-up conditions are optimized. The trypanocidal activity of the naphthoheterocycles shows no concordant behavior in relation to the parent compound. The most active compound is the naphthoimidazole (XI). -(PINTO, A. V.; PINTO, C. N.; PIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 0 publications
2
40
0
Order By: Relevance
“…As previously discussed for napthaquinones, the lipophylic character introduced by this appendage, as well as the presence of a methoxyl or a phenyl group, are factors that increase the trypanocidal activity. A characteristic of the synthesised naphthoimidazoles is that most of them present aromatic groups containing electron-releasing or electron-withdrawing groups attached to the imidazole ring (Pinto et al 1997b, Neves-Pinto et al 2000, Moura et al 2001. The results suggested that electronic factors related to the phenyl group were not relevant for the biological effect.…”
Section: Naphthoquinones and Derivativesmentioning
confidence: 70%
“…As previously discussed for napthaquinones, the lipophylic character introduced by this appendage, as well as the presence of a methoxyl or a phenyl group, are factors that increase the trypanocidal activity. A characteristic of the synthesised naphthoimidazoles is that most of them present aromatic groups containing electron-releasing or electron-withdrawing groups attached to the imidazole ring (Pinto et al 1997b, Neves-Pinto et al 2000, Moura et al 2001. The results suggested that electronic factors related to the phenyl group were not relevant for the biological effect.…”
Section: Naphthoquinones and Derivativesmentioning
confidence: 70%
“…The aminated compound 26a presents a high trypanocidal activity and the lack of previous reports in the literature on amino naphthofuranquinones has stimulated the synthesis of compounds with aminated groups linked to the furane ring. In another study of these series it was reported that lapachol 1 and -lapachone 2 display similar activities against T. cruzi, which were higher than that of crystal violet, whereas nor--lapachone 24, -lapachone 3, and lawsone were inactive [81]. Fig.…”
Section: Methodsmentioning
confidence: 94%
“…Pinto et al, have synthesized -lapachone derivatives through the reaction of these naphthoquinones with common reagents, leading to several heterocyclic compounds [81,82,95,96]. These were grouped as oxazolic, imidazolic, …”
Section: Trypanocidal Activity Of -Lapachone and Naphthoquinone Derivmentioning
confidence: 99%
See 1 more Smart Citation
“…Three naphthoimidazoles (N1-N3) derived from b-lapachone were the most active derivatives on the parasite (Pinto et al, 1997;Neves-Pinto et al, 2000Moura et al, 2001Moura et al, , 2004Silva et al, 2006Silva et al, , 2008a. These naphthoimidazoles were also effective on intracellular amastigotes and epimastigotes, in this latter form inhibiting DNA duplication (Menna-Barreto et al, 2005.…”
Section: Naphthoquinones and Derivativesmentioning
confidence: 95%